2013
DOI: 10.1080/00103624.2013.811523
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Germination and Growth of Slickspot Peppergrass in a New Medium with Two Compost Organic Fractions

Abstract: Slickspot peppergrass (Lepidium papilliferum) is an herbaceous biennal or possibly perennial "rare" endemic plant of the southwestern Idaho high desert listed as a threatened species. This plant establishes perennial seed banks, with seeds remaining dormant and viable for several years. This study aimed to enhance the germination and early growth of this plant by adopting a new medium, a nutrient-enriched agar solution, also added with humic acid (HA) and water-extractable organic matter (WEOM) fractions isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Higher contents of Ca and and vitamin C in tomato fruits have also been observed with vermi-compost application [15]. The composition of compost also affect the yield of crops such as tomato [9]. It has been reported that an application of vermi-compost enhances soil fertility [16] by providing with essential nutrient [17].…”
Section: Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher contents of Ca and and vitamin C in tomato fruits have also been observed with vermi-compost application [15]. The composition of compost also affect the yield of crops such as tomato [9]. It has been reported that an application of vermi-compost enhances soil fertility [16] by providing with essential nutrient [17].…”
Section: Blockmentioning
confidence: 99%
“…Thus, application of composts as a soil amendment has multiple benefits such as improving the soil health, minimizing the disease threat and controlling the soil erosion [8]. Moreover, the organic material mineralization improves nutrient availability, which in turn improves crop yield [9]. Vermi-compost materials are produced through the effective interaction of microbes and earthworms that could be used to improve the soil fertility [7].…”
Section: Introductionmentioning
confidence: 99%